Disease resistance and response against Vibrio anguillarum intestinal infection in European seabass (Dicentrarchus labrax) fed low fish meal and fish oil diets. Issue 67 (August 2017) - Torrecillas, S.; Caballero, M.J.; Mompel, D.; Montero, D.; Zamorano, M.J.; Robaina, L.; Rivero-Ramírez, F.; Karalazos, V.; Kaushik, S.; Izquierdo, M.
Abstract: The aim of this study was to assess the effects of low levels of dietary fish meal (FM) and fish oil (FO) on disease resistance and gut associated lymphoid tissue (GALT) response after an experimental intestinal infection with V. anguillarum in European sea bass ( Dicentrarchus labrax ) For that purpose, sea bass juveniles were fed one of four diets containing combined levels of FO and FM as follows: 20%FM/6%FO, 20%FM/3%FO, 5%FM/6%FO and 5%FM/3%FO during 153 days. At the end of the feeding trial, fish were subjected to either an in vivo exposure to a sub-lethal dose of V. anguillarum via anal inoculation or to an ex vivo exposure to V. anguillarum . Additionally, inducible nitric oxide synthase (iNOS) and tumor necrosis factor α (TNFα) gut patterns of immunopositivity were studied. Growth performance was affected by dietary FM level, however ex vivo gut bacterial translocation rates and survival after the in vivo challenge test were affected by dietary FO level. After 5 months of feeding, low dietary FM levels led to a posterior gut up-regulation of interleukin-1β (IL-1β) and TNFα, major histocompatibility complex-II (MHCII) and cyclooxygenase-2 (COX2), which in turn reduced the gut associated lymphoid tissue (GALT) capacity of response after 24 h post infection and conditioned European sea bass capacity to recover gut homeostasis 7 days post infection. Immunoreactivity to anti-iNOS and anti-TNFα presented a gradient of increased immunopositivity towards the anus, regardless of the dietary FM/FO fed. Strong positive anti-TNFα isolated enterocytes were observed in the anterior gut in relation to low levels of dietary FM/FO. Submucosa and lamina propria immunoreactivity grade was related to the amount of leucocyte populations infiltrated and goblet cells presented immunopositivity to anti-iNOS but not to anti-TNFα. Thus, reducing FO content from 6% to a 3% by VO in European sea bass diets increases ex vivo and in vivo gut bacterial translocation rates, whereas reducing FM content from 20% down to 5% up-regulates the expression of several posterior gut inflammation-related genes conditioning fish growth and GALT capacity of response after bacterial infection. Highlights: Reducing dietary FO levels from 6% to a 3% increases ex vivo and in vivo gut bacterial translocation rates. Diminishing FM dietary content from 20% to 5% up-regulates several posterior gut inflammation-related genes. Decreasing FM dietary content of FM from 20% to 5% limits European sea bass growth performance. FM or FO dietary content did not influence gut iNOS and TNFα immunolabelling along the gut. Strong positive anti-TNFα isolated epithelial cells similar to antigen-sampling cells were observed particularly in anterior gut.